Psychotic Experiences and Alternate Dimensions: A Thematic Analysis Exploring Frameworks of Psychotic Symptoms Among Saudis. (July 2021) - Hyder, Sanaa; Almutlaq, Nouf; Naseem, Mohammad Talal; Bilal, Lisa; Al-Subaie, Abdullah; Al-Habeeb, AbdulHameed; Altwaijri, Yasmin
Psychotic expression is influenced by unique contexts, including the individual's culture. The majority of research on psychotic experiences is quantitative and from Western, democratic societies. This article explores the explanatory models used by Saudis to describe psychotic experiences (i.e., hallucinations and delusions). Using open-ended responses to a structured psychosis screener embedded within a comprehensive mental health survey instrument, we conducted thematic analysis on data representing the psychotic experiences of 59 individuals. We found that Saudis report religious (e.g., Jinns) and cultural (e.g., modest clothing) frameworks alongside biological, psychological, and social mechanisms which potentially trigger an alternative reality for the affected individual. Our findings suggest it may be helpful for health care professionals to consider individual differences and work with religious leaders (e.g., Shaykhs ) to prevent misdiagnosis and mistreatment. In-depth qualitative studies are needed to examine trajectories of psychotic symptomatology among Saudis and the specific language used to describe such occurrences.